The Role of The Learning Environment in the Development Of Religious Character in Students at the Al-Quran Education Park (TPQ) - Triani, Galuh; Ismaniar, Ismaniar (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2025)
This research is motivated by the many current phenomena, namely the suboptimal use of the Al-Quran Reading Garden as a means of character building, such as the many children today who experience moral and ethical crises due to the negative influence of social media, online games and the environment weakening religious values among the younger generation. This study aims to explore the role of the learning intensity environment in supporting the development of religious character of students in the Al-Quran Education Garden (TPQ). The method applied in this study is a literature study, which involves an in-depth study of various sources, including scientific journals, books, and previous research related to the topic. The focus of the analysis in this study is the low level of religious character among TPQ students. The method used in this study is a literature study, namely by examining various sources such as scientific journals, books, and previous research that are relevant to the topic. The topic analyzed in this study is the role of the learning intensity environment on the religious character of students in TPQ. The results of this study indicate that: (1) a description of the phenomenon of learning intensity and student character in TPQ. In the context of learning in TPQ, learning intensity refers to the commitment of students to attend regularly, participate actively and carry out learning tasks seriously. (2) the role of the learning intensity environment on the development of religious character. The learning environment and learning intensity in TPQ not only focus on the ability to read the Qur'an, but also include the internalization of Islamic values in everyday life. Research on the relationship between the learning environment, learning intensity, and the development of religious character is important to optimize the function of TPQ in forming a generation of faith and noble morals. There is a significant relationship between the role of learning intensity and the formation of students' religious character in their daily application. Thus, this study confirms the importance of the role of the learning intensity environment on the religious character of students in TPQ. Therefore, this study can provide guidelines for TPQ managers to improve the quality of human resources and continuous evaluation.